Actinobacteria and Cyanobacteria Diversity in Terrestrial Antarctic Microenvironments Evaluated by Culture-Dependent and Independent Methods - Rego, Adriana; Raio, Francisco; Martins, Teresa P.; Ribeiro, Hugo; Sousa, António G. G.; Séneca, Joana; Baptista, Mafalda S.; Lee, Charles K.; Cary, S. Craig; Ramos, Vitor; Carvalho, Maria F.; Leão, Pedro N.; et al. (Frontiers in Microbiology, 2019)
Bacterial diversity from McMurdo Dry Valleys in Antarctica, the largest desert on earth, has become more easily assessed with the development of High Throughput Sequencing (HTS) techniques. However, some of the diversity remains unachievable by the power of sequencing. In this study, we combine cultivation and HTS techniques to survey Actinobacteria and Cyanobacteria diversity along different soil and endolithic micro-environments of Victoria Valley in McMurdo Dry Valleys. Our results have demonstrated that the Dry Valleys Actinobacteria and Cyanobacteria distribution is driven by environmental forces, in particular the effect of water availability and endolithic environments clearly conditioned the distribution of those communities. Data derived from HTS show that the percentage of Cyanobacteria decreases from about 20% in the sample closest to the water source to neglectable values on the last three samples of the transect with less water availability. Inversely, Actinobacteria abundance increases from the wet to the driest samples. Over 30% of the total HTS data set was composed of Actinobacterial strains, mainly distributed by 5 families: Sporichthyaceae, Euzebyaceae, Patulibacteraceae, Nocardioidaceae and Rubrobacteraceae. However, the 11 actinobacterial strains isolated in this study, belonged to Micrococcaceae and Dermacoccaceae families that were underrepresented in the HTS data set. A total of 10 cyanobacterial strains from the order Synechococcales were also isolated, distributed by 4 different genera (Nodosilinea, Leptolyngbya, Pectolyngbya, Acaryochloris). In agreement with the cultivation results, Lepyolyngbya was identified as dominant genera in the HTS data set. Acaryochloris genus were found exclusively in the endolithic sample and represented 44% of the total 16S rDNA sequences, although despite our efforts we were not able to properly isolate any strain from Acaryochloris genus. The importance of combining cultivation and sequencing techniques is highlighted, as we have shown that culture-dependent methods employed in this study were able to retrieve Actinobacteria and Cyanobacteria taxa that were not detected in HTS data set, suggesting that the combination of both strategies can be usefull to recover both abundant and rare members of the communities.